Lymphedema in Klippel-Trenaunay Syndrome: Is It Possible to Normalize?. (26th July 2016) - Godoy, Jose Maria Pereira de; Río, Angela; Domingo Garcia, Paloma; de Fatima Guerreiro Godoy, Maria
Abstract : The aim of this study is to report the results of intensive therapy of lymphedema associated with Klippel-Trenaunay syndrome. A 24-year-old female patient reported that her family had observed edema in her right leg and port wine stains from birth. For ten years, they consulted with different specialists in the region but the prognosis did not change and no specific treatment was found. In 2014, at the age of 24, with massive lymphedema, a leg ulcer, and recurrent infections, she started treatment at the Clínica Godoy in São José do Rio Preto. She was evaluated by clinical history, physical examination, water displacement volumetry, and bioimpedance. Intensive therapy (8 hours daily) was proposed using Manual Lymphatic Therapy (Godoy & Godoy), Cervical Stimulation Therapy, Mechanical Lymphatic Therapy, a grosgrain stocking adjusted several times a day, and the use of Unna boot in the region of the ulcer. The volume of edema was reduced by about 44% within the first week with further reductions in the following weeks and healing of the ulcer. Subsequently, it was possible to control and maintain the reduction in swelling with less intense treatment. It is possible to reduce and maintain the treatment results of lymphedema associated with Klippel-Trenaunay syndrome.